Autism phenotype versus registered diagnosis in Swedish children: prevalence trends over 10 years in general population samples. (28th April 2015) - Lundström, Sebastian; Reichenberg, Abraham; Anckarsäter, Henrik; Lichtenstein, Paul; Gillberg, Christopher
Abstract : Objective To compare the annual prevalence of the autism symptom phenotype and of registered diagnoses for autism spectrum disorder during a 10 year period in children. Design Population based study. Setting Child and Adolescent Twin Study and national patient register, Sweden. Participants 19 993 twins (190 with autism spectrum disorder) and all children (n=1 078 975; 4620 with autism spectrum disorder) born in Sweden over a 10 year period from 1993 to 2002. Main outcome measures Annual prevalence of the autism symptom phenotype (that is, symptoms on which the diagnostic criteria are based) assessed by a validated parental telephone interview (the Autism-Tics, ADHD and other Comorbidities inventory), and annual prevalence of reported diagnoses of autism spectrum disorder in the national patient register. Results The annual prevalence of the autism symptom phenotype was stable during the 10 year period (P=0.87 for linear time trend). In contrast, there was a monotonic significant increase in prevalence of registered diagnoses of autism spectrum disorder in the national patient register (P<0.001 for linear trend). Conclusions The prevalence of the autism symptom phenotype has remained stable in children in Sweden while the official prevalence for registered, clinically diagnosed, autism spectrum disorder has increased substantially. This suggests that administrative changes, affecting the registered prevalence, rather than secular factors affecting the pathogenesis, are important for the increase in reported prevalence of autism spectrum disorder.